Water: consumption, usage patterns, and residential infrastructure. A comparative analysis of three regions in the Lima metropolitan area - Rondinel Oviedo, Daniel Ricardo (2020)
This study examines the impact of infrastructure and residents’ water usage patterns (internal factors) and climate (external factor) on household water consumption. Through quantitative information from the service provider and qualitative data from 900 surveys in three areas with different socio-economic levels (high, middle and low) in the Lima metropolitan area, an average user profile is determined for each area. The results are further assessed and compared to establish the impact of internal and external factors on water consumption. These results help in establishing water handling policies and developing residential infrastructure design for efficient and sustainable use of water.